Re-visioning Ayi Kwei Armah’s Fragments: A Corpus Stylistic Analysis Using Wmatrix - Bonsu, Emmanuel Mensah; Nkansah, Samuel Kwesi (Íkala, Revista de Lenguaje y Cultura, 2024)
The numerous literary explorations of Ayi Kwei Armah’s novels reveal his aesthetic creativity and relevance in addressing African and diasporic issues that have contemporary relevance. Guided by two objectives, this corpus study set out to analyse the narration and thematisation of Armah’s Fragments (1970) through part-of-speech and semantic domain tags using Wmatrix. We compared Fragments as a target corpus with two other novels by Armah. Results of the analysis suggest that Armah alternates between homodiegetic narrative in character dialogues and monologues, which dominate the main heterodiegetic discourse narration. He also provides a critical perspective on the immediacy of a historic and instantaneous present by giving a specific past account that projects a possible continuity of events in Ghana and Africa. Additionally, Armah discusses the geographic mobility of characters as a metaphor for a quest for a place of being and identity. These findings illustrate the value of applying computational tools like Wmatrix to examine African literary texts and provide a base for further studies.